The Relationship Between Coping Strategies and Resilience for Students with People Pleaser Tendency - Desi Permata Sari; Komarudin Komarudin (Publikasi Indonesia, 2024)
Entering the early adult phase as a student, they will experience natural selection with a decrease in the number of people closest to them due to their busy schedules and different responsibilities. Some of the students try to maintain by always pleasing the people around them and even sacrificing their own needs and desires so that the pressure experienced will feel heavier, students tend to be people pleasers will experience complex problems in lectures with their own responsibility and desires that tend to continue to make others happy with them. This has an impact on stress, anxiety and even depression, so resilience is needed so that students who tend to be people pleasers can overcome and survive the pressure and responsibility in their lives as students. One of the factors that affects resilience is the coping strategy so that students tend to be people pleasers who have a good coping strategy will have good resilience as well. The purpose of this study is to determine the contribution of the relationship between coping strategies and resilience to students with a tendency to be people pleaser in the Special Region of Yogyakarta. Data collection was carried out using a coping and resilience strategy scale with a Likert scale model. The number of respondents in this study was 200 students with a tendency to be people pleasers in the Special Region of Yogyakarta with an age range of 18-24 years. The results of this study show that there is a significant positive relationship between coping strategies and resilience. The effective contribution result was 59.8% and the correlation coefficient in this study was 0.773. The significance test in this study is 0.000 < 0.05.